2002
DOI: 10.4269/ajtmh.2002.66.435
|View full text |Cite
|
Sign up to set email alerts
|

Platelet adhesion to dengue-2 virus-infected endothelial cells.

Abstract: Abstract. Platelets in circulation normally do not adhere to resting endothelial cells. However, in response to vascular injury they adhere to stimulated endothelium and thereby play an essential role in hemostasis and thrombosis. Infection with dengue-2 virus can cause illness accompanied by thrombocytopenia and hemorrhage. Increased adherence of platelets to stimulated endothelial cells could contribute to the thrombocytopenia. In this study, adherence of radioisotopically labeled platelets to 1) unstimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 24 publications
2
81
1
5
Order By: Relevance
“…20 Studies report that the platelet activation (with elevated surface P-selectin) and apoptosis (with increased caspases and phosphatidylserine (PS) expression) are associated in the early days of dengue infection. 21,22 Reports also show that the activation of complement factor C3 followed by binding of C5b-9 complex to platelet surface is significantly linked with platelet destruction and thrombocytopenia in these patients. [23][24][25] 11 of 61 patients studied by Mitrakul et al, had destruction as a main cause for thrombocytopenia, as revealed by platelet kinetic study.…”
Section: Discussionmentioning
confidence: 97%
“…20 Studies report that the platelet activation (with elevated surface P-selectin) and apoptosis (with increased caspases and phosphatidylserine (PS) expression) are associated in the early days of dengue infection. 21,22 Reports also show that the activation of complement factor C3 followed by binding of C5b-9 complex to platelet surface is significantly linked with platelet destruction and thrombocytopenia in these patients. [23][24][25] 11 of 61 patients studied by Mitrakul et al, had destruction as a main cause for thrombocytopenia, as revealed by platelet kinetic study.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that the decrease in the TEER before 48 h after addition of PBMCs is due to activation of PBMCs by adherence to the DV-2-infected endothelial cell monolayer. After infection with dengue virus, endothelial cells express adhesion molecules (Krishnamurti et al, 2002). PBMCs which attached to infected endothelial cells are activated, and activated PBMCs may produce cytokines that act locally and increase plasma leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells can be infected with dengue virus in vitro (Bunyaratvej et al, 1997;Huang et al, 2003;Killen & O'Sullivan, 1993). Dengue virus infection induces cytokine production (Avirutnan et al, 1998;Bosch et al, 2002) and alters the expression of adhesion molecules on endothelial cells (Krishnamurti et al, 2002). Although endothelial cells are not massively infected, there is evidence of dengue virus infection of endothelial cells in vivo (Gubler & Zaki, 1998;Hall et al, 1991;Jessie et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, it is possible that the formation of PAIgM could be linked to the increased vascular permeability, which is characteristic of DHF. A recent in vitro study has reported on the adhesion of platelets to dengue virus-infected endothelial cells [29]. Activated platelets associated with dengue virus and antidengue virus IgM as well as dengue virus-infected endothelial cells may be involved in the mechanism of the increased vascular permeability associated with DHF [30,31].…”
Section: Discussionmentioning
confidence: 99%